Star of the Sea de Joseph O’Connor - Mikowski, Sylvie (Presses universitaires de Caen, 2007)
This paper examines how in his latest novel, Joseph O’Connor has recourse to most of the devices defined by Linda Hutcheon as « metafictional historiography », insofar as the book, instead of offering the reader a realistic account of the Irish Great Famine in the manner of Liam O’Flaherty’s Famine, questions the reliability of any historical discourse, including those on the Famine. The novel plays with archetypes, each character alluding to a specific social position, but also to previous literary representations. The whole cultural context of the Famine is evoked, thanks to intertextual allusions to English or Irish authors, such as Charles Dickens or Oscar Wilde, but also to forms of « popular » culture, namely songs, ballads, legendary figures such as Jack the Ripper, or popular magazines such as Punch. The inclusion in the world of fiction of extracts from real archives aims at blurring the lines between history and fiction, thus foregrounding the verbal, constructed nature of both forms of narration. This way of questioning the capacity of historical discourse to depict the complexities of the past must be set in relation with a long line of so-called Irish « historical novels », which each in its own fashion, deviates from the rules of the genre such as Georg Lukács defined it through his analysis of Walter Scott’s novels. O’Connor’s ironic, metafictional mode is also inspired by the prevailing intellectual debate going on in contemporary Ireland, revolving around the critique of the nationalist transformation of history into myth, a critique which has led to the rise of the « new History » of Edwards and Moody to a revision, or rewriting, of Irish history, a revision which has itself been lately criticised and corrected. The result is O’Connor’s most brilliant piece of fictional writing so far.